Apolipoprotein E and neurological disease: therapeutic potential and pharmacogenomic interactions. (August 2007) - Laskowitz, Daniel T; Vitek, Michael P
The apolipoprotein E (apoE) polymorphism is emerging as a uniquely important genetic modifier that affects functional outcome from both acute and chronic neurological injuries. Recent attention has focused on common denominator mechanisms by which apoE might affect brain injury and/or brain repair responses in clinically diverse diseases. Although endogenous apoE likely serves several adaptive functions in the injured CNS, there is growing evidence that its effect on modifying brain inflammatory responses and providing protection from excitotoxic injury may be central to its protective properties. A more complete understanding of the role that apoE plays in the injured brain has led to novel therapeutic strategies for both acute and chronic neurological disease.